Decoding the genetic interplay between stress and Alzheimer’s disease. - Milligan Armstrong, Ayeisha Grace (Curtin University, 2024)
Alzheimer’s disease (AD) has a complex aetiology involving genetic and environmental factors. This thesis explores how genetic and epigenetic variation in stress-related genes influences AD risk and progression. Key findings include associations between genetic variants, DNA methylation, and AD-related phenotypes, involving cognition and brain volume changes. Additionally, shared genetic architectures and biological pathways underpinning stress-traits and AD were identified. These findings will assist in the identification of potential therapeutic targets and advancing precision medicine approaches.